Geochemical characteristics and tectonic implications of igneous rocks from the Santos Basin and adjacent areas - Su, Jinglin; Sun, Jing; Yang, Liu (Frontiers in Earth Science, 2025)
The increasing presence of igneous rocks in hydrocarbon-bearing basins are drawing more attention. While the roles they play during the hydrocarbon generation and reservoir formation remain poorly understood, yet a detailed inspection of their geochemical features within the corresponding tectonic context is lacking. This study compiles comprehensive geochemical data, including major and trace elements, as well as the isotopic composition of igneous rocks spanning from 147 to 40 Ma at the Santos Basin and adjacent area. Based on their geochemical signatures and tectonic settings, the igneous rocks are classified and analyzed. During 147–40 Ma, the studied location had a complex tectonic background which demonstrated a transition from the mantle plume to continental rift, then to mantle plume, corresponding to the discovered geochemical characteristics. This progression corresponds to the breakup of the West Gondwana and the opening of the South Atlantic Ocean. The findings highlight the potential positive role of igneous rocks in hydrocarbon systems, revealing their potential favorable roles. These results provide a robust foundation for future exploration and research in analogous basins.